Institusi Pengajian Pondok di Selangor: Kajian terhadap Sejarah dan Perkembangan: Institusi Pengajian Pondok di Selangor: Kajian terhadap Sejarah dan Perkembangan - Ab Rahim, Aisyah; Mohd Nor, Mohd Roslan (Online Journal of Research in Islamic Studies, 2020)
The establishment of Pondok institution has proven to be of great benefit to the Muslim community. In addition to being the Malay Muslim identity, pondok institutions has not only facilitate easier Islamic study through systematic education system but also create job opportunities, improve social standards and generate many local leaders in the fields of religion, education and leadership. The objective of this study is to study the institutions of pondok in Selangor and to re-introduce this traditional education system and its importance to the current generation. This study will also examine the factors that lead to the decline of pondok, identify it’s weaknesses and efforts made to restore and improve pondok institution especially in Selangor.